2015
DOI: 10.1039/c5nr03243a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of fluorine content in graphene: towards large-scale production of stoichiometric fluorographene

Abstract: The availability of well-defined modified graphene derivatives such as fluorographene, graphane, thiographene or hydroxygraphene is of pivotal importance for tuning the resulting material properties in numerous potential applications. A series of fluorinated graphene with various contents of fluorine was synthesized by a simple fluorination procedure in an autoclave with a nitrogen/fluorine atmosphere at different exposure times and temperatures. To investigate the composition, structure and properties all sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
144
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 38 publications
6
144
0
Order By: Relevance
“…[14] Graphene can be also modifiedb yh ydrogenation. [17] Other methods are based on the fluorination of graphene by using variousf luorinating agentss uch as SF 6 ,X eF 2 ,o rf luorine at elevated temperatures and pressures. [15] Analogous to graphane, the fully fluorinated graphene with composition C 1 F 1 is called fluorographene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Graphene can be also modifiedb yh ydrogenation. [17] Other methods are based on the fluorination of graphene by using variousf luorinating agentss uch as SF 6 ,X eF 2 ,o rf luorine at elevated temperatures and pressures. [15] Analogous to graphane, the fully fluorinated graphene with composition C 1 F 1 is called fluorographene.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Other methods are based on the fluorination of graphene by using variousf luorinating agentss uch as SF 6 ,X eF 2 ,o rf luorine at elevated temperatures and pressures. [6] It has been also reported that fluorinated graphene is ah igh-quality insulator with high Young's modulus. [19] The bandgapo f fluorographene can be tuned in the range from 0eV( unmodified graphene) to 3.4 eV for stoichiometric fluorographene.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40] It is also shown that the defluorination can be achieved by exposing FG to ultraviolet irradiation for long time in aromatic solvents like toluene and benzene. 23,41 On a different report, the possibilities of defluorination by the solvent based treatment of fluorinated graphene is also discussed, where the semi-ionic C-F bonds were removed from fluorinated graphene upon its treatment with dipolar solvents such as N-methyl-2-pyrrolidinone (NMP) via ultra-sonication. 23 Recently, the authors have demonstrated that the interactions between polar solvents and C-F bond in FG are highly crucial for the solvent assisted defluorination, and even moderately polar solvents such as tetrahydrofuran (THF) can interact with FGO to remove C-F bonds in a day or two without any extensive sonication.…”
Section: Fluorination Of Graphene-synthesis and Control Of Fluorinementioning
confidence: 99%
“…23,41 On a different report, the possibilities of defluorination by the solvent based treatment of fluorinated graphene is also discussed, where the semi-ionic C-F bonds were removed from fluorinated graphene upon its treatment with dipolar solvents such as N-methyl-2-pyrrolidinone (NMP) via ultra-sonication. 23 Recently, the authors have demonstrated that the interactions between polar solvents and C-F bond in FG are highly crucial for the solvent assisted defluorination, and even moderately polar solvents such as tetrahydrofuran (THF) can interact with FGO to remove C-F bonds in a day or two without any extensive sonication. 40 This method also proves that other oxygen functionalities are kept intact even after 30 days of THF treatment indicating that the reaction is quite selective.…”
Section: Fluorination Of Graphene-synthesis and Control Of Fluorinementioning
confidence: 99%
See 1 more Smart Citation